2020
DOI: 10.1158/2326-6066.cir-19-0514
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between Colon Cells and Macrophages Increases ST6GALNAC1 and MUC1-sTn Expression in Ulcerative Colitis and Colitis-Associated Colon Cancer

Abstract: Patients with ulcerative colitis have an increased risk of developing colitis-associated colon cancer (CACC). Changes in glycosylation of the oncoprotein MUC1 commonly occur in chronic inflammation, including ulcerative colitis, and this abnormally glycosylated MUC1 promotes cancer development and progression. It is not known what causes changes in glycosylation of MUC1. Gene expression profiling of myeloid cells in inflamed and malignant colon tissues showed increased expression levels of inflammatory macroph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 53 publications
1
55
0
Order By: Relevance
“…UC is recurrent and difficult to heal, and it is referred to as “deathless cancer” due to its serious impact on patients’ quality of life. UC is closely related to the development of colon cancer [ 5 ], which is difficult to cure. The pathogenesis of UC has not been clarified, and the possible underlying mechanisms include bacterial infection, intestinal mucosal barrier dysfunction, and genetic, dietary, environmental, immunological, and psychological factors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…UC is recurrent and difficult to heal, and it is referred to as “deathless cancer” due to its serious impact on patients’ quality of life. UC is closely related to the development of colon cancer [ 5 ], which is difficult to cure. The pathogenesis of UC has not been clarified, and the possible underlying mechanisms include bacterial infection, intestinal mucosal barrier dysfunction, and genetic, dietary, environmental, immunological, and psychological factors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of inflammation-associated microsatellite alterations was increased during the progression of UCAN (23). Glycosyltransferase ST6 N-acetylgalactosaminide alpha-2,6-sialyltransferase 1 (ST6GALNAC1) was induced by M2-like macrophages, and ST6Galnac1 alters the glycosylation status of the oncoprotein mucin 1, thereby promoting cancer development and progression in UC (24). However, the exact mechanisms underlying the pathogenesis of UCAN remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…UC was an incurable and recurrent IBD disease, that eventually could progress to colon cancer. [ 3 ] Although a large number of studies had demonstrated that it was related to many factors, such as genes, environment, immunity, and infection, its exact etiology had not been clearly elucidated so far. [ 1 ] The histopathology showed that lots of immune cells would infiltrate in the mucosal layer of the intestinal wall, such as neutrophils, macrophages, dendritic cells, and T lymphocytes, etc.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] UC was sometimes difficult to cure, it was easy to relapse, and then the patients could form polyps, even malignant turn into colon cancer. [ 3 ] Epidemiology showed that the incidence of UC was increasing year by year globally. [ 4 ] It was widespread in 20 to 40 years old adults, and there was no gender difference.…”
Section: Introductionmentioning
confidence: 99%